Improving the Student's Speaking Skill by Using Tik Tok App at the Tenth Grade of SMA Negeri 1 Gido in 2022/2023 - Yuris Puji Listiani Zebua; Trisman Harefa; Elwin Piarawan Zebua; Kristof Martin Efori Telaumbanua (Journal on Education, 2023)
Speaking is one of the important skills that must be learnt by the students. However, the students had several problems in learning speaking which caused the Minimum Competence Criterion (MCC) were not able to achieve by the students. They were lack of vocabulary, the lack of students in think in short time when want to say, and the students were not able to identify the generic structure of song lyric. Therefore, the aim of research was to improve the students’ speaking skill in use Tik Tok App at the tenth grade of SMA Negeri 1 Gido in 2022/2023. The subject of the research was the tenth grade consisted of 19 students. The research was conducted by using Classroom Action Research (CAR) and it was applied in two cycles. Each cycle consisted of several procedures they were planning, action, observation, and reflection. The researcher used observation sheet, field notes, and test as the instruments of research. The result of Cycle I showed that most of the students were not able to achieve the MCC where no student There were 10 students (52,63%) who got mark classified in “Good” level. There were 9 students (47,36%) who got mark classified in “Adequate” level. And there were 0 students (0%) who got mark classified in “Less” level. The average of students’ writing skill in Cycle I was 52,63. While in Cycle II, it showed that all of students have been achieved the MCC where 13 students in “Excellent” level (72.22%), 5 students in “Good” level (27.78%), and there was no student in “Fair” level and “Poor” level. The average of students’ speaking skill in Cycle II was 84,21% Based on the result above, it proved that Tik Tok App increased the students’ speaking skill at the tenth grade of SMA Negeri 1 Gido in 2022/2023.